2021
DOI: 10.1097/aud.0000000000001105
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensory Tinnitus Diagnosis: Diagnostic Value of Existing Criteria

Abstract: Background: Tinnitus can be influenced by changes in somatosensory afference from the cervical spine or temporomandibular area, then called somatosensory or somatic tinnitus (ST). In 2018, a new set of diagnostic criteria for ST was agreed upon by a large group of ST experts. Currently, however, it still requires extensive and specific expertise to diagnose ST correctly. The next step in the development of easily applicable diagnostic criteria is to assess the diagnostic value of each individual criterion. Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 32 publications
(43 reference statements)
2
19
0
1
Order By: Relevance
“…Furthermore, a higher prevalence of women in the somatic tinnitus population has been reported [37], which raises questions regarding the somatic component in the hyperacusis population. A recent article by Michiels, et al [40] showed a higher prevalence of hyperacusis in a group of patients with a higher degree of somatic tinnitus, which is in line with the earlier study by Schecklmann, et al [8]. However, other studies did not demonstrate this finding [41].…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, a higher prevalence of women in the somatic tinnitus population has been reported [37], which raises questions regarding the somatic component in the hyperacusis population. A recent article by Michiels, et al [40] showed a higher prevalence of hyperacusis in a group of patients with a higher degree of somatic tinnitus, which is in line with the earlier study by Schecklmann, et al [8]. However, other studies did not demonstrate this finding [41].…”
Section: Discussionsupporting
confidence: 67%
“…Az elvégzett carotis-vertebralis ultrahangvizsgálat alacsonyabb arányát magyarázhatja a vizsgálat korlátozottabb elérhetősége, illetve a pandémia hatása. A nyakigerinc-röntgenvizsgálat szintén fontos, különösen a szometoszenzoros tinnitusformák esetén [8]. A jelenleg elemzett beteganyagon nyakigerinc-röntgenvizsgálatra nagy arányban került sor (80%), az ábrázolt eltérések közül pedig a spondylosis és a spondyloarthrosis volt messze a leggyakoribb.…”
Section: Megbeszélésunclassified
“…Nowadays, the idea that changes in brain regions outside the auditory pathway, in particular the somatosensory pathway, the emotional and the attentional systems, could trigger the development and maintenance of tinnitus is more widely accepted in the community [15]. Additional non-invasive human studies support the involvement of somatosensory pathways in tinnitus [16] and of attentional and limbic networks with possible interactions with the auditory network [17].…”
Section: Introductionmentioning
confidence: 99%